Sympathovagal imbalance decades after atrial septal defect repair: a long-term follow-up study. (20th May 2021) - Alstrup, Mathias; Karunanithi, Zarmiga; Maagaard, Marie Ø; Poulsen, Steen H; Hjortdal, Vibeke E
Abstract: : OBJECTIVES: Recent evidence suggests that patients with a corrected atrial septal defect (ASD) have higher morbidity and mortality. An abnormal autonomic regulation of the heart may be a part of the explanation for this. Our objective was to study heart rate variability (HRV) in adults with a corrected ASD as a prominent tool to investigate the autonomic regulation of the heart. METHODS: Autonomic cardiac function was investigated in adults with either a surgically closed or percutaneously closed ASD and healthy control subjects. A 48-h Holter monitor was performed on each participant and HRV was assessed. RESULTS: A total of 17 patients with surgically closed ASDs, 18 percutaneously closed ASDs and 18 controls were included. The mean age in the surgical group, percutaneous group and controls was 32 ± 9, 28 ± 7 and 32 ± 10 years, respectively. The mean time since closure was 19 ± 8 years for the surgical group and 15 ± 5 years for the percutaneous group. The surgically closed ASD patients showed decreased HRV in all six parameters studied when compared to the controls. Similarly, the percutaneously closed ASDs showed decreased HRV in three out of six parameters when compared to controls. CONCLUSIONS: Adults with an ASD, whether closed surgically or percutaneously, have impaired HRV compared to their age- and sex-matched controls, more so in the patients with a surgically closed ASD. Clinical trial registration number: ClinicalTrials.gov (identifier: NCT03565471). Abstract : Atrial septal defect (ASD) is the third most common congenital heart defect [1].